Turbulent structure effects due to ordered surface roughness - Zambri Harun; Ashraf Amer Abbas; Eslam Reda Lotfy; Morteza Khashehchi (Alexandria Engineering Journal, 2020)
The effects of ordered surface feature in the form of converging-diverging riblets are investigated experimentally on an airfoil. Riblet sheets are applied onto the surface of NACA 0026 airfoil at a yaw angle of α=0°,±10°, Riblet height of h = 1 mm, and riblet spacing of s = 2 mm. The length of the riblets strip is approximately 7.5% in chord percentage. At a low friction Reynolds number of Reτ ≈ 200, at an adverse pressure gradient parameter of β ≈ 0.5–0.8, the riblet surfaces cause the boundary layer and turbulence intensity profiles to change drastically. Upon exposure to riblets, both the boundary layer and turbulence intensity profiles closely follow that of the favourable pressure gradient (FPG) flows. Without riblets, the velocity profile shows a very high wake, the flow has a very thin layer of the logarithmic region and a highly energized inner region. From the spectral analysis, without riblets, the inner region contains energized λx+ = 1000 features and large-scale features measuring 20δ, (δ is the boundary layer thickness). The spectral analysis reveals that riblets of any type break these 20δ features in the near-wall into smaller features 3–4δ. The analysis further reveals that the large-scale events of riblet surfaces are similar, but not for the smooth surface.